GAMBARAN PASIEN PREEKLAMPSIA DAN EKLAMPSIA DI RSUD DR. H. CHASAN BOESORIE PERIODE TAHUN 2018-2020 - Febrianti, Febrianti; Nagib , Adib; Armaijn , Fadhilah (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Preeclampsia is a specific condition in pregnancy characterized by placental dysfunction and maternal response to systemic inflammation by endothelial activation with coagulation. While eclampsia is an acute disorder in pregnant women in labor or postpartum characterized by seizures and or coma, which previously obtained symptoms of severe preeclampsia. According to the World Health Organization (WHO), preeclampsia cases are seven times higher in developing countries than in developed countries. The prevalence of preeclampsia in developed countries is 1.3% - 6%, while in developing countries is 1.8% - 18%. This study is a descriptive study using patient data contained in medical records. The sample in this study was all mothers who had preeclampsia and eclampsia at DR. H. Chasan Boesorie Hospital in the period 2018-2020 amounting to 127 cases. The technique of sampling used is total sampling. The results of this study found 127 cases of preeclampsia and eclampsia consisting of classification of severe preeclampsia (74.8%) mothers aged 20-35 years (67.7%), multipara (51.0%), irregular ANC (74.8%), obesity (52.8%), caesarean delivery (74.0%), normal baby weight (70.9%), gestational age 37-40 weeks (60.6%).The conclusions of the results of this study are most common in severe preeclampsia, maternal age 20-35 years, mothers with multipara, not routine ANC, obesity, cesarean delivery, normal baby weight, and gestational age 37-40 weeks.